Clinical factors associated with non-diabetic renal disease in diabetic latin american patients, histopathological findings, and predictive model (2022)
ABSTRACT: The prevalence of diabetes was reported by the World Health Organization from 180 million in 1980 to 422 million in 2014, differentiating those patients who have diabetes. Still, it is not the cause of kidney damage. It is actually in the presence of non-diabetic renal disease (NDRD) or who, in addition to having diabetic nephropathy, simultaneously suffers from another illness that aggravates kidney function and is susceptible to a therapeutic intervention other than glycemic control that allows for improving renal survival. The present analysis of 201 biopsies from native kidneys in diabetes mellitus patients from the pathology department of the University of Antioquia at the San Vicente Hospital clinical laboratory was a retrospective cohort study. The kidney biopsy report that 41% of patients had diabetic nephropathy, 16% mixed, and 43% NDRD, the most frequent histological finding was focal segmental glomerulosclerosis; in the univariate and multivariate analysis, two independent predictors were identified, each year above the mean age (56 years) increases the risk of presenting NDRD (OR, 1.05; 95% CI, 1.02–1.09; p = 0.002) in the KB. The diabetic retinopathy significantly decreases the occurrence of NDRD (OR, 0.23; 95% CI, 0.09–0.60; p = 0.002). Our findings on the potential predictive strategies, the model with the clinical variables age, diabetic retinopathy, and time of diabetes offered the best predictive performance. The area under the discrimination curve was 0.75 (95% CI, 0.67-0.81) with an acceptable Hosmer Lemeshow test, and calibration can be useful when deciding whether to perform a kidney biopsy..